The Community Ecology of Herbivore Regulation in an Agroecosystem: Lessons from Complex Systems. (11th December 2019) - Vandermeer, John; Armbrecht, Inge; de la Mora, Aldo; Ennis, Katherine K; Fitch, Gordon; Gonthier, David J; Hajian-Forooshani, Zachary; Hsieh, Hsun-Yi; Iverson, Aaron; Jackson, Douglas; Jha, Shalene; Jiménez-Soto, Estelí; et al.
Abstract: Whether an ecological community is controlled from above or below remains a popular framework that continues generating interesting research questions and takes on especially important meaning in agroecosystems. We describe the regulation from above of three coffee herbivores, a leaf herbivore (the green coffee scale, Coccus viridis), a seed predator (the coffee berry borer, Hypothenemus hampei), and a plant pathogen (the coffee rust disease, caused by Hemelia vastatrix) by various natural enemies, emphasizing the remarkable complexity involved. We emphasize the intersection of this classical question of ecology with the burgeoning field of complex systems, including references to chaos, critical transitions, hysteresis, basin or boundary collision, and spatial self-organization, all aimed at the applied question of pest control in the coffee agroecosystem.